Haptomerus maculosus, a new species of the tribe Myorhinini from Zambia (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman; Nakládal, Oto (Zootaxa, 2019)
The new species Haptomerus maculosus Borovec & Nakládal, sp. n. is described, illustrated and compared with its related species. A key to all Haptomerus species is presented. New data for other species of Haptomerus are presented. The relationships of Haptomerus species are discussed with particular attention to the relationships of species from the Afrotropical region and those from southern Europe.